Implementasi pembelajaran Pendidikan Agama Islam menggunakan video cerita dalam pembentukan karakter siswa yang islami - Muh. Arifin (Action Research Journal, 2021)
Islamic Religious Education (PAI) is one of the compulsory subjects ranging from basic to higher education for followers of the Islamic religion. The purpose of this study is to implement Islamic religious education learning using video stories in the formation of Islamic characters. This type of research is Classroom Action Research (CAR) with four stages of implementation. The subjects in this study were 18th graders of SDN 02 Talun. Data collection techniques in this study were obtained from interviews, written test observations and documentation. The data obtained were analyzed by calculating the average mastery of individual and classical learning. The success indicator in this study is for individual learning completeness if the proportion of students' correct answers is more than the predetermined KKM and for classical learning completeness if at least 85% of all students have reached the KKM. The results of this study are in cycle 1, students whose scores reach the minimum completeness criteria are 14 students with a percentage of 77.78%. Then for students who have not achieved completeness at least 4 students with a percentage of 22.22%. For cycle 2, students whose scores reach the minimum completeness criteria are 16 students with a percentage of 88.89%. Then for students who have not achieved completeness, there are at least 2 students with a percentage of 11.11% as well. So it can be concluded that the use of video stories can increase the formation of Islamic characters.